2017
DOI: 10.1163/1568539x-00003420
|View full text |Cite
|
Sign up to set email alerts
|

Time partitioning in mesocarnivore communities from different habitats of NW Italy: insights into martens’ competitive abilities

Abstract: Most studies focused on species coexistence have been directed at the differential use of habitat and food resources; nonetheless, the differential use of the diel cycle may enhance the coexistence of same-sized species. We investigated the activity patterns of mesocarnivores (red fox (Vulpes vulpes), European badger (Meles meles), pine marten (Martes martes), stone marten (M. foina)) in NW Italy via camera-trapping. We hypothesized that the smallest species would tend to avoid competition by selecting time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 82 publications
0
32
1
2
Order By: Relevance
“…We found weak evidence for temporal segregation with strong temporal overlap between martens and fishers. Temporal segregation between martens and fishers has only been reported in one study to date (McCann et al, ) but has been documented in other sympatric mesocarnivores (Harrington et al, ; Monterroso, Alves, & Ferreras, ; Monterroso et al, ; Torretta et al, ). Martens and fishers exhibited largely crepuscular activity patterns consistent with other studies (Arthur & Krohn, ; Drew & Bissonette, ; Powell et al, ; Zielinski, Spencer, & Barrett, ).…”
Section: Discussionmentioning
confidence: 98%
“…We found weak evidence for temporal segregation with strong temporal overlap between martens and fishers. Temporal segregation between martens and fishers has only been reported in one study to date (McCann et al, ) but has been documented in other sympatric mesocarnivores (Harrington et al, ; Monterroso, Alves, & Ferreras, ; Monterroso et al, ; Torretta et al, ). Martens and fishers exhibited largely crepuscular activity patterns consistent with other studies (Arthur & Krohn, ; Drew & Bissonette, ; Powell et al, ; Zielinski, Spencer, & Barrett, ).…”
Section: Discussionmentioning
confidence: 98%
“…What may be the origin of such different behavioral attitudes in these two prototypically similar (Larroque et al, ) species? While the pine marten was described as mainly nocturnal with bouts of daily activity (Clevenger, ) or facultative nocturnal (Monterroso, Alves, & Ferreras, ), recently Torretta et al () and Fonda, Torretta, Balestrieri, and Pavanello () showed through camera‐trapping in Northern Italy that it may be better defined as cathemeral, with up to 60% of diurnal recordings. In Tuscany, available radiotracking data indicate that the pine marten is active throughout the diurnal cycle (Del Fante, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both species coexist over a large area (Mitchell‐Jones et al, ) and prefer forested habitats; nonetheless, when syntopic, the pine marten generally occupies forested areas, while the stone marten occurs in rural and suburban areas (Vergara, Cushman, Madeira, & Ruiz‐González, ; Virgós, Zalewski, Rosalino, & Mergey, ). Stone marten association with fragmented and urbanized habitats has been explained as the result of competition with the pine marten (Delibes, ), although the mechanisms which should make the latter more competitive are still not clear (but see Torretta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the sharing of limited resources, including ranging areas and food, is expected to trigger competition between species occupying similar niches (de Boer & Prins, 1990). Physiological and behavioural adaptations would promote niche partitioning, thus favouring the coexistence amongst species living in sympatry (Razgour et al, 2011;Torretta et al, 2017;Pudyatmoko, 2019).…”
Section: Introductionmentioning
confidence: 99%